PEMETAAN ALIRAN PEMIKIRAN DAKWAH DITINJAU DARI PERIODISASI GERAKAN DAKWAH DAN KONSEP KEILMUAN - Asna Istya Marwantika (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2015)
Dakwah activity in the society has grown rapidly, but it was developed still practical and yet provide a meaningful contribution in the theoretical realm. Therefore, it would need to do the literature search to identify the period of the dakwah movement of the time of the Prophet Muhammad until today. In addition it should also identify the defining concept of dakwah from the academics, have it dakwah concept is tailored to the needs of society and the development of post- positivistic era or dakwah still require elaboration of new concepts to address the challenge of the complexity of the society.